Sites and politics of religious diversity in southern Europe : the best of all gods - Mapril, José; Blanes, Ruy (International studies in religion and society., 2013)
Moving beyond the current media verves, this book debates, from a critical perspective, case studies on the sites and politics of religious diversity in Southern Europe.